Unmasking Gendered Language Patterns in Social Media Discourse - Yuzar, Ella; Rahman, Fadhlur; Sari, Dwhy Dinda; Zanzibar, Zanzibar (Saree: Research in Gender Studies, 2023)
This study investigates the complex realm of gendered discourse within the social media landscape, with an emphasis on revealing and analyzing language patterns. This research employs content analysis as a research methodology, utilizing Twitter's Application Programming Interface to extract tweets that include the hashtags #womenempowerment, #feminist, #menempowerment, and #malechauvinist for the purpose of this study. The decision to focus on these specific hashtags was deliberate, as they represent the spectrum of gender-related discourse, including emancipation, feminism, men's emancipation, and male chauvinism. The prevalence of these hashtags in online discussions demonstrates the various ways Twitter users interact with and express their views on these critical gender issues. This paper explored the intricacies of language usage, uncovering valuable insights that could be pertinent to discussions surrounding gender representation and equality. The findings provide researchers, practitioners, and society with valuable insights into effectively navigating the constantly changing landscape of gendered discourse on social media.   Abstrak: Dengan penekanan pada analisis pola bahasa, penelitian ini menyelidiki ranah wacana gender yang rumit dalam interaksi online di media sosial. Sebagai metodologi penelitian, penelitian ini menggunakan analisis konten. Untuk melakukan ini, Twitter's Application Programming Interface digunakan untuk mengekstrak tweet dengan tagar #womenempowerment, #feminist, #menempowerment, dan #malechauvinist. Fokus pada tagar-tagar ini digunakan dengan tujuan khusus karena mereka mewakili berbagai topik terkait gender, seperti emansipasi, feminisme, emansipasi laki-laki, dan chauvinisme laki-laki. Tagar-tagar ini muncul dalam diskusi dan interkasi online, menunjukkan berbagai cara pengguna Twitter berinteraksi dan menyatakan pendapat mereka tentang isu-isu gender yang penting. Lebih jauh, penelitian ini menemukan berbagai aspek penggunaan bahasa dan memberikan perspektif penting yang sangat relevan dengan pembicaraan tentang representasi gender dan kesetaraan. Hasil ini membantu para peneliti, praktisi, dan masyarakat mengatasi wacana gender di media sosial yang terus berubah.